Sugarcane harvest time for processing and technological quality of brown sugar - Tischler, André Luis; Jeronimo, Elisangela Marques; Lúcio, Alessandro Dal’Col; Sari, Bruno Giacomini; de Melo, Patrícia Jesus; Boesso, Francine Fricher [UNESP]; Diel, Maria Inês; de Lima Tartaglia, Francieli (FapUNIFESP (SciELO), 2021)
The objective of this work was to evaluate the optimal harvest time of ten genotypes of sugarcane (Saccharum officinarum) for the processing and quality of brown sugar. The experiment was carried out in a randomized complete block design in a 3×10 factorial arrangement in split plots, with three harvest times and ten sugarcane genotypes, in the state of São Paulo, Brazil. The qualitative parameters of brown sugar were evaluated by Scott-Knott’s test, at 5% probability. The harvest season in September, known as the middle of the harvest, is the most suitable for the production of brown sugar due to the higher of ºBrix values of cane, ºBrix of the broth, pol of brown sugar, and total reducing sugars in this period. The harvesting of the sugarcane genotypes in June-July is the most favorable for the production of brown sugar for the color characteristics a*, b*, L*, and chroma; however, it is also the period of production of brown sugar with a lower sugar content. The third harvest season (November) is the least recommended for brown sugar production due to the higher fiber and purity values. The most suitable genotype for brown sugar production and quality is ’IACSP04-704’.
Época de colheita da cana-de-açúcar para processamento e qualidade tecnológica de açúcar mascavo
Keywords: genotype; production; reducing sugars; Saccharum officinarum; ºBrix